Advances in accounting behavioral research. Vol. 18 - Schmitt, Donna Bobek (Advances in accounting behavioral research,, 2015)
Advances in Accounting Behavioral Research publishes high-quality research encompassing all areas of accounting including financial, auditing, taxation, managerial and information systems, addressing a broad range of issues that affect the users, preparers and assurers of accounting information. Further, this research incorporates theory from, and contributes knowledge and understanding to, applied psychology, sociology, management science, and behavioral economics.